2017
DOI: 10.18203/2320-1770.ijrcog20173495
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of first trimester bleeding

Abstract: INTRODUCTIONUltrasonography is one of the most important and useful diagnostic tool in the field of modern medicine. Being non-invasive, safe and without hazards of radiation, it has gained wide acceptability, as an integral part of basic investigative procedures.The convenience, high portability, rapidity, and accuracy are few of the advantages of ultrasound over the other procedures. In the last two decades, ultrasound has become an essential diagnostic imaging modality in the field of obstetrics and is bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…16 According to a study by Tiparse A et al in 2017, 74 (37%) patients were diagnosed as threatened abortions, 14 (7%) cases were diagnosed as incomplete abortions, and 6 (3%) cases were diagnosed as complete abortions. 17 The results of these studies well correlated with the given study, 32 cases (40%) were threatened abortion, 28 cases (35%) be incomplete abortions, and 12 cases (15%) were diagnosed as complete abortions.…”
Section: Discussionsupporting
confidence: 81%
“…16 According to a study by Tiparse A et al in 2017, 74 (37%) patients were diagnosed as threatened abortions, 14 (7%) cases were diagnosed as incomplete abortions, and 6 (3%) cases were diagnosed as complete abortions. 17 The results of these studies well correlated with the given study, 32 cases (40%) were threatened abortion, 28 cases (35%) be incomplete abortions, and 12 cases (15%) were diagnosed as complete abortions.…”
Section: Discussionsupporting
confidence: 81%
“…The major causes are abortion, ectopic, and molar pregnancy. 6 The estimated incidence of partial hydatidiform mole (PHM) is 1 in 700 pregnancies whereas the incidence of complete hydatidiform mole (CHM) is around 1 in 1500-2000 pregnancies. 7,8 Approximately 20% of complete moles and 0 to 3.5% of partial moles lead to persistent gestational trophoblastic disease (GTD).…”
Section: Discussionmentioning
confidence: 99%
“…The invaluable role of these landmarks, the gestational sac and fetal biometry in diagnosing pathological pregnancies and predicting the pregnancy outcome has been clearly documented. 10,11 Maihotra J in his prospective evaluation of 150 patients with first trimester bleeding found that ultrasonography helped in establishing the correct diagnosis in 32% of clinically misdiagnosed cases. 12 He concluded that ultrasonography was the only imaging modality, by which an accurate assessment of first trimester bleeding can be done from the diagnostic and prognostic point of view.…”
Section: Discussionmentioning
confidence: 99%